2013
DOI: 10.5551/jat.14092
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Response to Aspirin in Chinese Stroke Patients is Independent of Genetic Polymorphisms of COX-1 C50T and COX-2 G765C

Abstract: Aim: Aspirin resistance (AR) is common in Chinese stroke patients taking antiplatelet medications; however, few studies have documented the role of cyclooxygenase (COX)-1 C50T and COX-2 G765C polymorphisms in AR. The aim of this study was to investigate the prevalence of AR in Chinese stroke patients and the relationships between AR and COX-1 C50T and COX-2 G765C polymorphisms, and to evaluate the effect of these polymorphisms on platelet response to aspirin. Methods: We prospectively enrolled 634 Chinese stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
1
17
2
Order By: Relevance
“…We found that the prevalence of AR and ASR was 20.6 and 5.3%, respectively, and that diabetes mellitus was associated with AR. These findings were in accordance with previous studies [5, 18, 27]. Further, aside from variant P2Y1 (rs1371097), we found no significant differences in the distribution of the other variants between the AR + ASR group and AS group.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We found that the prevalence of AR and ASR was 20.6 and 5.3%, respectively, and that diabetes mellitus was associated with AR. These findings were in accordance with previous studies [5, 18, 27]. Further, aside from variant P2Y1 (rs1371097), we found no significant differences in the distribution of the other variants between the AR + ASR group and AS group.…”
Section: Discussionsupporting
confidence: 93%
“…Polymorphisms in COX -2 rs20417 and COX-1 C50T have been reported to be associated with impaired aspirin responsiveness [13, 14]. However, in both a previous study [18] and this study, these polymorphisms were not found to be associated with AR in acute IS patients. P2Y12 and P2Y1 are platelet membrane receptors and play a key role in platelet aggregation, thrombosis and the pharmacology of antiplatelet therapy [9].…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations